Pelatihan CAD CAM Dan Kegunaannya Pada Dunia Industri Untuk Mahasiswa Mesin Politeknik Negeri Bengkalis - Zulhendri, Zulhendri; Yuliarman, Yuliarman; Chadry, Rivanol; Junaidi, Junaidi; Andriyanto, Andriyanto (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Computer-Aided Design (CAD) technology is a form of automation that helps designers to improve drawings, specifications, and elements related to design using special graphic effects and computer program calculations. Technology that combines computers with CAD software with CNC (Computer Numeric Control) production machines, where this technology is used for various products in the environment and architecture, electronics, and aerodynamics (air dynamics), automotive engineering and product design. While CAM (Computer Aided Manufacturing) is a technology for planning, arranging and controlling product manufacturing with the help of computers. CAD-CAM is a compulsory course taught to students of Mechanical Engineering Study Program and other study programs related to engineering or machine design. One of the study programs that studies CAD-CAM is the D4 Mechanical Production and Maintenance Engineering Study Program from the Department of Mechanical Engineering, Bengkalis State Polytechnic, but it has not been implemented in depth. Based on this, this community service was carried out for students of the Mechanical Engineering Department of the Bengkalis State Polytechnic. Through this community service, training was provided to students about CAD-CAM materials and their use in the industrial world such as in the milling and lathe machining process and in the 3D printing process. In addition, there was also a sharing of experiences in operating 3D printing brands Ender-K1 owned by the Bengkalis State Polytechnic CNC laboratory so that it could operate optimally. On this occasion, a 3D printing tool, the clarity ender 3.V3.SE brand, was also handed over. Keywords: CAD-CAM, CNC, solidwork, ZW3D, 3D-printing,